2020
DOI: 10.1126/scitranslmed.aay8456
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of TGFβ1 activation overcomes primary resistance to checkpoint blockade therapy by altering tumor immune landscape

Abstract: Despite breakthroughs achieved with cancer checkpoint blockade therapy (CBT), many patients do not respond to anti–programmed cell death-1 (PD-1) due to primary or acquired resistance. Human tumor profiling and preclinical studies in tumor models have recently uncovered transforming growth factor–β (TGFβ) signaling activity as a potential point of intervention to overcome primary resistance to CBT. However, the development of therapies targeting TGFβ signaling has been hindered by dose-limiting cardiotoxicitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(215 citation statements)
references
References 66 publications
10
159
1
Order By: Relevance
“…Studies found that TGF-β was associated with poor clinical outcomes and limited the response of anti-PDL1 therapy which was attributed to T cell exclusion in urothelial and colorectal cancer ( Mariathasan et al, 2018 ; Tauriello et al, 2018 ). TGF-β1, the universal isoform of TGF-β, presents in many human cancers and contributes to anti-PD1 resistance ( Martin et al, 2020 ). Tumor-derived chemokines recruit immunosuppressive cells including Tregs, macrophages and MDSCs to the TME to create an immunosuppressive but tumor-supportive environment, interfering the immunotherapy targeting adaptive immune resistance ( Roussos et al, 2011 ).…”
Section: Primary Resistancementioning
confidence: 99%
“…Studies found that TGF-β was associated with poor clinical outcomes and limited the response of anti-PDL1 therapy which was attributed to T cell exclusion in urothelial and colorectal cancer ( Mariathasan et al, 2018 ; Tauriello et al, 2018 ). TGF-β1, the universal isoform of TGF-β, presents in many human cancers and contributes to anti-PD1 resistance ( Martin et al, 2020 ). Tumor-derived chemokines recruit immunosuppressive cells including Tregs, macrophages and MDSCs to the TME to create an immunosuppressive but tumor-supportive environment, interfering the immunotherapy targeting adaptive immune resistance ( Roussos et al, 2011 ).…”
Section: Primary Resistancementioning
confidence: 99%
“…As a direct TGF-β-targeting agent, the high-affinity artificial TGF-β1 antibody SRK-181 has been employed successfully in anti-PD-1 cancer treatments to override immunotherapy resistance. Equally, the co-administration of SRK-181 and anti-PD-1 has also demonstrated increased anti-tumour effects and survival benefits in bladder cancer-bearing mice by increasing infiltering CD8+ T cells and decreasing immunosuppressive myeloid cells [ 145 ]. Another chemical TGF-β inhibitor, tranilast, which was originally developed as an antiallergic drug, has also demonstrated proven anti-fibrosis and anti-tumour effects.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…TGF-β is expressed in cancer, stromal and immune cells in three isoforms, TGF-β1, β2, and β3. Several pan-cancer gene expression analyses have shown that TGF-β1 is the primary isoform expressed in tumors, while TGF-β3 is less frequently observed and TGF-β2 is rarely detected and mainly serves to regulate normal cardiac function and hematopoiesis, which helps explain the failure of earlier pan-TGF-β targeting therapies due to toxicity-related adverse events [108,147,148] . The most common proposed mechanisms of TGF-β-driven ICB resistance are CD8+ T cell exclusion via fibroblast differentiation and subsequent stromal remodeling and inhibition of CD4+ T helper cell differentiation to the immune-activating T-helper (Th)1 effector cell phenotype, as these conditions have been reproduced in various mouse tumor models and effectively treated by combined targeting of TGF-β and the PD-1/PD-L1 axis [149][150][151][152] .…”
Section: Clinical Trials: Targeting Emp To Improve Immunotherapy Of Cmentioning
confidence: 99%